Pengangkatan Orang Percaya Ke Awan-awan - Bert Haniko (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2021)
The purpose of this investigation is to find out the Rapture of believers to the clouds, which is the same as the Apostle Paul in I Thessalonians 4: 13-18. The result is (1) Believers do not need to mourn the death of believers (2) Gathering of Believers With God (3) Simultaneous Appointment of Believers (4) Welcoming God in Space (5) Believers' Life Forever with God in heaven. So it was concluded that oaring believers need not fear when they die (die), because when we believe in the Lord Jesus as Lord and Savior in our lives, we will surely experience the lifting of clouds to meet God in the clouds. This is a statement from the apostle Paul as an Apostle of grace, so that the doctrine of the adoption of believers in the clouds must have taken place.